ENGLISH DIPTHONGS [eɪ], [aɪ], [aʊ] PRONUNCIATION PROBLEMS ENCOUNTERED BY SEVENTH SEMESTER STUDENTS OF ENGLISH LITERATURE STUDY PROGRAM IN STIKUBANK UNIVERSITY ACADEMIC YEAR OF 2018 - Fitri Wulandari; Katharina Rustipa (Dinamika Bahasa dan Budaya, 2022)
This final project concerns about the problem of pronouncing English diphthongs conducted by students majoring in English Literature at Stikubank University, which aims to analyze English diphthongs and what are the causes of the problem. This research uses descriptive quantitative research method. The subjects of this study were taken as many as 7 students from the English Literature department at the Stikubank University Semarang academic year of 2018. The data collected through student pronunciation tests from WhatsApp, and also recorded via voice notes from WhatsApp, then the recorded data was transcribed. The results of this research show that the most difficult English diphthong to pronounce correctly is diphthong [aʊ] which has a presentation of 39.93%, then for diphthong [eɪ] as much as 34.48%, and the lowest diphthong [aɪ] is 27.59%. From these results it can be concluded that students still have to practice a lot so that they can be easily understood and avoid misunderstandings. Keywords: English Diphthong, Pronunciation Error, Monophthongization